DEVELOPMENT AND VALIDATION OF STABILITY INDICATING REVERSED PHASE HIGHPRESSURE LIQUID CHROMATOGRAPHY METHOD FOR SIMULTANEOUS ESTIMATION OF METFORMIN AND EMPAGLIFLOZIN IN BULK AND TABLET DOSAGE FORM - Swarupa P, Geetha; Rao K, Lakshmana; KRS, Prasad; Babu K, Suresh (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: To develop accurate, fast, simple, and precise reversed-phase high-pressure liquid chromatography method for simultaneous determination of the binary mixture of metformin (MET) and empagliflozin (EMPA) in dosage forms. Methods: The method uses a mobile phase consisting of phosphate buffer, acetonitrile, methanol (15:80:5 v/v/v), an octadecyl silica C-18 column (4.6Â mmÂ Ã—Â 250Â mm,Â 5Â Î¼Â particleÂ size)Â inÂ isocraticÂ mode,Â detectionÂ wavelengthÂ ofÂ 227Â nm,Â andÂ aÂ flowÂ rateÂ ofÂ 1Â mL/minutes. Results:Â TheÂ measuredÂ retentionÂ timesÂ forÂ METÂ andÂ EMPAÂ andÂ wereÂ 2.528Â andÂ 4.140Â minutes,Â respectively.Â TheÂ percentageÂ recoveriesÂ ofÂ METÂ andÂ EMPAÂ wereÂ 101.12%Â andÂ 100.55%,Â respectively.Â TheÂ relativeÂ standardÂ deviationÂ forÂ assayÂ ofÂ tabletsÂ wasÂ foundÂ toÂ beÂ <2%.Â TheÂ correlationÂ coefficientÂ forÂ METÂ andÂ EMPAÂ wasÂ foundÂ toÂ beÂ 0.9990.Â TheÂ limitÂ ofÂ detectionÂ andÂ quantificationÂ forÂ METÂ wasÂ 0.10Â Âµg/mLÂ andÂ 0.31Â Âµg/mLÂ andÂ forÂ EMPAÂ 0.01Â Âµg/mLÂ andÂ 0.03Â Âµg/mL. Conclusion:Â TheÂ methodÂ wasÂ fast,Â accurate,Â precise,Â andÂ sensitiveÂ henceÂ itÂ canÂ beÂ employedÂ forÂ routineÂ qualityÂ controlÂ ofÂ tablets containing both drugs in quality control laboratories and pharmaceutical industries. Keywords: Empagliflozin, Forced degradation method, Metformin, Reversed-phase high-performance liquid, Stability-indicating assay.